Analysis of the Impact of Unemployment Rates on Economic Growth in Java: The ARDL Panel Approach in Current Economic Dynamics - Alfa Ramadhan; Asep Munir Hidayat; Billy Tejaarief; Kenedi Kenedi; Anti Wulan Agustini (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Economic growth plays an important role in the development of a country and the welfare of its people. One indicator that influences economic growth is the unemployment rate, which can reduce productivity and cause social problems. This research aims to analyze the long-term and short-term effects of unemployment rate, investment, inflation, and Human Development Index (HDI) on economic growth in the provinces of Java Island, as well as to assess the long-term adjustment mechanism (Error Correction Term) in each region. This research uses secondary data analysis with a correlational quantitative approach. The research results show that in the long term, unemployment rate, investment, inflation, and HDI have a significant influence on economic growth. In the short term, the influence between variables differs across provinces: East Java shows significant influence from all variables, Central Java is influenced by unemployment rate, inflation, and HDI, while DKI Jakarta is influenced by unemployment rate and investment. Banten, West Java, and DIY do not show significant influence in the short term. The long-term adjustment mechanism (Error Correction Term) is significant in East Java, but not significant in other provinces. Based on these findings, it can be concluded that macroeconomic variables have different influences across regions in Java Island, with East Java as the province that is most consistent in achieving long-term economic growth stability. The results of this research provide important implications for the formulation of region-based economic policies that consider the differences in characteristics and economic responses across provinces.